Human papillomavirus types in cases of squamous cell carcinoma of head and neck in Colombia (2013)
ABSTRACT: Estimating the type-specific prevalence of human papillomavirus (HPV) in head and neck cancer (HNSCC) is helpful in predicting the impact of HPV immunization. Objective: To estimate the overall prevalence, and gender and age-specific prevalence of HPV in HNSCC. Method: This cross sectional retrospective study was carried out in four pathology laboratories of Medellin, Colombia. HPV testing was performed by GP5+/6+ PCR-based RLB and HPV 16 and 18 type-specific PCR. Results: 175 primary HNSCC cases consecutively diagnosed between 1999 and 2008 with confirmed diagnosis and amplifiable DNA were included. Overall HPV prevalence was 18.9%. HPV was found in 23.9%, 17.5% and 13.3% of the oral cavity, larynx and oropharynx cases respectively. Among HPV positive cases, 82% were HPV 16 and 18% were HPV 18. No other HPV genotypes were identified. Most patients were males. Male patients were younger that their female counterparts, particularly in oral cavity cancer cases. Conclusion: HPV 16 and 18 genotypes were found in nearly 20% of HNSCC cases in Colombian patients. The impact of HPV vaccination for the prevention of HNSCC in this population deserves further evaluation.